Dengue virus infection: a major cause of acute hepatic failure in Thai children - Poovorawan, Yong; Hutagalung, Yanee; Chongsrisawat, Voranush; Boudville, Irving; Bock, Hans L. (Annals of tropical paediatrics, 2006)
Background: Acute hepatic failure (AHF) can be caused by a variety of viruses, drugs, toxins and metabolic disorders. Aims: A prospective study was conducted to determine the aetiology and outcome of AHF in Thai children aged 1-15 years. Methods: All serum samples were tested for anti-HAV IgM, HBsAg, anti-HBc IgM, anti-HCV, anti-HEV IgM and anti-dengue IgG and IgM. Further individual investigations were done according to the clinical impression. Results: Forty subjects were enrolled from 14 centres during February 2000 to December 2001. Five cases were excluded owing to a lack of evidence of encephalopathy. The causes of AHF were dengue infection in 12 (34.3%), Wilson disease in 2 (5.7%), T-cell lymphoma in 2 (5.7%), ischaemic hepatitis in two (5.7%), haemophagocytic syndrome in one (2.8%), CMV in 2 (5.7%), Reye syndrome in one (2.8%) and unknown in 13 (37.1%) patients. The fatality rate was 68.6%. Eight of 24 (33.3%) deaths were caused by dengue infection. Conclusions: Improvements in sanitation and socio-economic status as well as the implementation of hepatitis B vaccine in the Extended Programme on Immunization (EPI) are likely to be the reasons for the observed absence of AHF caused by hepatitis A and B. The study showed that dengue infection, on the other hand, was a major cause of AHF in Thailand.